Global, regional, and national time trends in ischaemic heart disease incidence over three decades (1990–2019): an age-period-cohort analysis of the global burden of disease study 2019 - Tang, Juan; Hu, Shaobo; Liu, Xiaozhu; Li, Huan; Kuang, Lirong; Zhang, Lei; Cao, Wenzhai; Zhang, Ting; Guan, Xiaoyan; Li, Lang; Zhang, Yutao; Peng, Shengxian; et al. (Frontiers in Cardiovascular Medicine, 2024)
To assess the prevailing trends in the incidence of ischemic heart disease (IHD) across 204 countries and territories from 1990 to 2019, and to elucidate their correlations with age, period, and birth cohort, a comprehensive analysis was conducted.From 1990 to 2019, we employed the Global Burden of Disease Study (GBD) Results Tool in conjunction with an age-periodcohort model. This approach facilitated the estimation of annual percentage changes in incidence, referred to as net drifts, encompassing the overall population. Additionally, we calculated annual percentage changes spanning ages 15-19 to 95+ years, denoted as local drifts. Furthermore, our analysis involved determining period and cohort relative risks, elucidating the effects associated with distinct periods and birth cohorts.Globally, 21,203,479 (95% uncertainty interval [UI]: 18,799,322-23,704,124) cases of IHD occurred in 2019.There were 33 countries with at least 100000cases. Between 1990 and 2019, the net drift of IHD incidence exhibited a range from -1.7% per year (95% confidence interval [CI]: -1.79, -1.61) in countries with a high socio-demographic index (SDI) to 0.08% per year (95% CI: 0.05, 0.11) in countries with a low SDI. Age effects across all countries and genders demonstrated an increasing trend over time, indicating age as a significant risk factor for IHD. Moreover, period and cohort effects in higher SDI countries exhibited a more rapid decline in both genders compared to lower SDI countries. The findings indicated that nations with a higher SDI manifested overall favorable trends in the relative risk of IHD incidence, both across time and in successive younger birth cohorts.The incidence of IHD serves as a valuable and accessible indicator for assessing trends in IHD provision, spanning from early youth through later life. Enhancements in IHD prevention have the potential to mitigate risks for successively younger cohorts and, over time, redistribute the risk across all age groups. Despite global declines in IHD incidence over the last three decades, decreasing trends in incidence have slowed and, in some countries, flattened. Many countries have experienced unfavorable period and cohort effects.